Composition and sampling depth of olivine in carbonate-rich olivine lamproites of the Kaapvaal craton - Merrily M. Tau; Geoffrey H. Howarth; Andrea Giuliani; Sinelethu Hashibi (Mineralogy and Petrology, 2025)
Olivine represents the main constituent (40–50 vol%) of carbonate-rich olivine lamproites (CROL) and their xenocrystic cores offer great potential for characterizing the sub-continental lithospheric mantle (SCLM). We present electron probe microanalysis (EPMA) and laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS) data for olivine cores and rims from 11 on-craton CROL localities from the Kaapvaal craton. Olivine xenocrysts are predominantly Mg-rich [Mg# > 89; Mg# = 100 × Mg/(Mg + Fe)], constituting > 95% of the olivine core population. Cores with Mg# of 93–95 and low Ca (< 400 ppm) are unusually abundant in the CROLs, indicating sampling of highly refractory SCLM. Except for the localities Star and Marsfontein, peridotitic olivines from near the lithosphere-asthenosphere boundary (LAB) are rare, and the SCLM is sampled mainly up to ~ 180 km, consistent with the scarcity of deeply derived Cr-poor olivine megacrysts and sheared peridotites. CROLs that sample harzburgitic olivine from the deep lithosphere (> 160 km) feature high diamond grades. Assuming lamproite derivation from the bottom of the lithosphere or deeper, the 160–220 km depth interval beneath the localities Bellsbank, Klipspringer, and Roberts Victor, which show main olivine sampling modes at < 160 km, is likely dominated by eclogite lithologies which is in line with the record of xenoliths and diamond inclusions. Parental melts of the CROLs likely assimilated SCLM components, a process which influenced melt Mg# and the budget of Mn, Co, Zn, Li, and Ti in olivine based on the observed correlation between average core and rim compositions. Conversely, the concentrations of Al, Na, Ca, and Cu in magmatic olivine rims and, therefore, lamproite melts appear to be related to the thermal conditions (and entrainment depth) of the assimilated SCLM.

Kimberlite pre-conditioning of the lithospheric mantle and implications for diamond survival: a case study of olivine and mantle xenocrysts from the Koidu mine (Sierra Leone) - Geoffrey H. Howarth; Andrea Giuliani; Yannick Bussweiler; Merrily Tau; Sinelethu Hashibi; Philip E. Janney; Tom E. Nowicki (Mineralium Deposita, 2025)
The diamond potential of kimberlites is generally determined using indicator minerals (i.e., xenocrysts), entrained by the parent magma while ascending through the sub-continental lithospheric mantle (SCLM). It is becoming increasingly apparent that olivine can also be used to understand mantle sampling depth, using the Al-in-olivine thermometer, and to constrain the extent of diamond-destructive metasomatism in the SCLM. To further current understanding of vertical sampling and diamond preservation in the SCLM, we present geochemical results for kimberlitic olivine of the Koidu mine (Sierra Leone). We combine our olivine data with pressure-temperature estimates from available olivine diamond inclusions, clinopyroxene xenocrysts, and eclogite xenoliths to visualise the vertical distribution of lithologies in the SCLM beneath Koidu. In agreement with the absence of peridotitic olivine and low abundance of olivine diamond inclusions in the lower SCLM, megacrysts appear to dominate the material sampled from the lowermost lithosphere. At shallower levels a distinct eclogite-dominated region is observed (160-180 km) whereas the SCLM at depths of 110-150 km is heterogeneous comprising depleted harzburgite/dunite, lherzolite, and eclogite. Diamonds are predominantly eclogitic with pressure-temperature estimates for diamondiferous eclogites of 150-190 km within the eclogite-dominated region. The near absence of diamonds sampled from near the lithosphere-asthenosphere boundary is attributed to diamond destruction by extensive infiltration of proto-kimberlite melts leading to metasomatism of the eclogite and peridotite substrate and megacrysts formation. Widespread metasomatism of the deepest reaches of the SCLM sampled by kimberlites elsewhere suggests that Koidu does not represent an isolated case and the extent of diamond-destructive metasomatism can be constrained using olivine xenocrysts.